(untitled) (Indian Journal of Public Health Research & Development, 2023)
Abstract Background: Hearing loss in Diabetic patients is global problem WHO report has a suggestion that 50% of hearing loss in Diabetic patients is preventable. Hence various grades of hearing loss has to be evaluated Method: 250 hearing loss patients,aged between 20 to 50 years were studied by pure tone audiometry, by audiometry degree, type and configuration of hearingwas assessed. General examination was done by otoscopy followed by pure tone audiometry in which manual audiometry was used. Results: 123 (49.2%) had moderate loss, 89 (35.6%) moderate severe, 38 (15.2%) severe hearing loss, Associated clinical manifestation were 86 (34.4%) had parasthesia, 60 (24%) had skin disease, 50 (20%) had visual problems, 54 (21.6%) had lack of sleep. Conclusion: In this pragmatic study it is concluded that there is strong correlation between Diabetes mellitus and hearing threshold levels especially at higher frequencies. Long duration and uncontrolled diabetes has more implications over hearing threshold. This study will help the ENT surgeon to diagnose the severity of hearing loss and treat efficiently to avoid morbidity mortality and social withdrawl.